The impact of feeding date palm by products on the reproduction of Awassi ewe in the Qatari environment - Atta, Muzzamil; Mahgoub, Osman; Kadim, Isam T; Al-Marri, Saleh J; Fadlalla, Imad M T (Asian Journal of Agriculture and Rural Development, 2024)
The study aimed to examine the effect of feeding date palm with a product-based ration on the productivity of Awassi ewes raised intensively in the Qatari environment. The two matching total mixed rations consisted primarily of Rhodes and barely grains (CD), discarded dates, and crushed fronds (NCD). Forty-four Awassi ewes were divided into two matching groups. The groups were allocated randomly to the dietary treatments in a randomized block design experiment of 2 rams (mature fertile male sheep). Dates of service and lambing, ewes’ weights at conception and lambing, and lambs’ weights at birth and weaning (at 90 days of age) were registered. The type of diet had no effect on percentages of conceived and lambed ewes: gestation (150 ± 3.4 days), lambing interval periods (326 ± 17.4 days), litter size (117 ± 37.9 lambs/100 ewes), litter birth weight (3.9 ± 1.07 kg/lambing ewe), litter weaning weight (20.4 ± 5.83 kg/lambing ewe), weight of weaned lambs/ewe/year, weight of weaned lambs/kg of ewe weight/year, and weight of weaned lambs/kg0.75 of ewe weight/year. The NCD group had higher feed intakes (dry matter, DM, metabolizable energy, ME, and crude protein, CP) than the CD group. However, in terms of cost, NCD had a low cost of daily feed intake (1.88 vs. 2.42 riyals/ewe/day) and a cost of one kilogram of weaned lambs/ewe/year (30.8 vs. 43.2 riyals). It was concluded that feed based on date palm byproducts provided a performance not different from conventional feed but at a low feed cost.